Implementasi Quality Function Deployment Melalui House of Quality Untuk Rencana Peningkatan Kualitas Website Learning Management System - Dwihatami, Dinary; Siregar, Suzanna Lamria (Journal of Information System Research (JOSH), 2024)
The development of 21st century technology has triggered ecosystem transformation in various sectors, including education. The implementation of Learning Management System (LMS) is one form of educational evolution by providing an efficient centralized learning system. Hendevane Training Partner (HTP), a training institution in Depok City, has adopted LMS as part of its services. Through the LMS website, participants can access various training materials, interact with mentors and fellow participants, and take online exams. Evaluation of the quality of LMS services is important to ensure participant satisfaction. The Quality Function Deployment (QFD) method is used to analyze and improve service quality, with a focus on understanding participant needs. The results of QFD are then implemented through the House of Quality (HOQ) to determine improvement priorities. This study aims to apply QFD and HOQ in improving the quality of LMS services at HTP, with the hope of contributing to increasing participant satisfaction and the development of the distance learning system as a whole. The results of this study are the priority of improvement in navigation speed (changing pages).